(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Esthetic beauty clinic is many people’s need, but the critical point of protection for its patients is still weak. Many problems often affect the patients of esthetic beauty clinic. Patients deserve protection of medical service standard constituting something important to maintain and to improve. Forensic and toxicological medical sciences are needed to give adequate protection to the patients of esthetic beauty clinic. Through its scientific method, the state could prove, prevent, and take action all at once against the esthetic beauty clinics operated haphazardly. The clinic selling, concocting, using, and promoting hazardous and toxic drug and cosmetic can be detected and acted on, while forensic test was intended to prove the consequence or output of esthetic beauty clinic’s service. This scientific method supported the protection and the right of patients of esthetic beauty clinic, corresponding to the constitution.